A Abadia de Northanger (1817) de Jane Austen e o gótico racionalizado: uma leitura política - Buzian, Maria Luiza Ribeiro (Universidade Federal de São Carlos, 2025)
Through a concept that contested the supremacy of neoclassical ideals, emphasizing an aura that was barbaric, irrational, chaotic and mysterious, the Gothic style made its way into the lives of English readers. We can see this in the case of Catherine Morland, a reader of Jane Austen's novel Northanger Abbey (1817). therefore aim to investigate the issue of the rationalization of the Gothic in this novel, based on the discussion proposed by Sandra Guardini Vasconcelos (2002) in her book “Dez lições sobre o romance inglês do século XVIII” – on the emergence of the English novel genre, and also from the method of levels of interpretation in Fredric Jameson's (1992) political reading, contemplating the literary text as a socially symbolic act. I argue that in the novel in hand it would already be possible to observe the idea of the rationalization of the Gothic, not at first reading, since it is directed at a new audience of readers, of the bourgeois order, with this genre appearing at a time of change, just as in the society of the regency period, marked by the transition between aristocracy and bourgeoisie.
Northanger Abbey (1817) by Jane Austen and the rationalized gothic: a political reading
Keywords: Jane Austen; Literatura inglesa; Gótico; Crítica dialética; English literature; Gothic; Dialetics criticism; LINGUISTICA, LETRAS E ARTES::LETRAS::TEORIA LITERARIA; 4. Educação de Qualidade